Altitude and life tables of Culex quinquefasciatus (Diptera Cucilidae) populations - GARCÍA-G., CAROLINA; ESCOVAR-C., JESÚS; LONDOÑO-B., YESICA; MONCADA-A., LIGIA (Revista Colombiana de Entomología, 2010)
The differences in development time, survival, mortality and life expectancy were determined for three populations of the mosquito Culex quinquefasciatus from three temperature zones in the Cundinamarca department of Colombia: Mosquera (2516 m, 15°C), Fusagasugá (1728 m, 22°C) and Girardot (269 m, 33°C). The larvae and adults from each population were kept in laboratory conditions similar to those of their place of origin. Survival and mortality for each colony were recorded daily. For the statistical analysis, the Kruskal Wallis test was used with Bonferroni´s modification. Development times by site were as follows: Mosquera 15.05 days, Fusagasugá 10.62 days and Girardot 7.72 days. Significant differences were only found between Mosquera and Girardot, but by analysis of the development time for larvae separately, were significant differences among all three populations. Intrapopulation differences in the three cohorts were not significant. Survival and mortality of the pre-reproductive stages showed no significant differences in the three cohorts and survival showed a type-1 curve. The life expectancy for a recently oviposited egg from Girardot was 26.06 days, from Fusagasugá it was 24.12 days and from Mosquera it was 40.77 days. These data show that Culex quinquefasciatus has been adapting to higher elevation zones with lower temperatures without detriment to life table parameters.